(untitled) (Journal of Environmental Bioremediation and Toxicology, 2022)
The rate of environmental degradation is an increasing trend globally and most especially in many developing nations where it has food production implications. This deterioration in environmental quality is mostly attributed to population growth, urbanization, industrialization, and unsustainable agricultural practices. The Niger Delta region of Nigeria is the oil and gas province of Nigeria. The activities of illegal crude oil refiners, theft, vandalism, etc. are common within the region, thereby leading to the degradation of major biophysical environmental matrices and conditions. Plant and fish-based diets are the major food sources for humans within the Niger Delta region. This review focuses on the implications of artisanal crude oil refining (ACOR) on sustainable food production in the Niger Delta region of Nigeria. The review found that the activities of artisanal crude oil refiners are harming the vegetation cover, altering the physicochemical and microbial composition of the soil, and releasing hydrocarbons into the environment, which are absorbed by vegetation leading to an increase in human and biodiversity contamination from ACOR as well as loss of arable farmlands, uncontrolled bush burning, and increased cases of soil erosion. Therefore, ACOR activities are having negative effects on food security, which is characterized by food availability, accessibility, stability, and utilization. Hence, there is a need to curtail the activities of ACOR through the issuance of operational liens followed by stricter regulations and monitoring of harmful emissions released during the processes.